MAKNA YANG HILANG DALAM TERJEMAH AL_QUR'AN: STUDI TERHADAP SURAT AL-QASHASH AYAT 10 VERSI KEMENTERIAN AGAMA REPUBLIK INDONESIA - Dalimunthe, Alwisyah (STAIN Sultan Abdurrahman Kepulauan Riau, 2023)
The translation of the Qur'an has a great contribution in understanding the Qur'an for non-Arabic people, especially Indonesians. One of the weaknesses of translating Arabic into Indonesian is the lack of Indonesian vocabulary. As a result, in some translations there is a loss of original meaning, such as in the translation of the Qur'an issued by the Ministry of Religious Affairs of the Republic of Indonesia (Kemenag RI). The discussion in this article focuses on the meaning of the words